Theranostics application of tumor-initiating cell probe TiY in non-small cell lung cancer - Lee, Yong-An (2023)
Background: Tumor-initiating cells (TIC) often elude conventional cancer treatment, which results in metastasis and cancer relapse. Recently, studies have begun to focus on the TIC population in tumors to provide better therapeutic options. Previously, we have reported the successful development of a TIC-specific probe TiY with the binding target as vimentin. While a low concentration of TiY showed a TIC visualization, at a high concentration, TiY induced selective toxicity onto TIC in vitro. In this study, we aim to assess TiY's applicability in theranostics purposes, from in vivo visualization to therapeutic effect toward TIC, in cancer mouse models. Methods: We performed cell experiments with the TIC line model derived from resected primary non-small cell lung cancer (NSCLC) patient tumor. The animal model studies were conducted in mice of NSCLC patient-derived xenograft (PDX). TiY was intravenously delivered into the mice models at different concentrations to assess its in vivo TIC-selective staining and therapeutic effect. Results: We demonstrated the TIC-selective identification and therapeutic effect of TiY in animal models. TiY treatment induced a significant ablation of the TIC population in the tumor, and further molecular study elucidated that the mechanism of TiY is through vimentin dynamics in TIC. Conclusion: The results underscore the applicability of TiY for cancer treatment by selectively targeting soluble vimentin in TIC.